VD_FINDINFO HC / 2022 / 186 vom 16. Februar 2022 - VD Tribunal cantonal (2022)
PROPRIÉTÉ PAR ÉTAGES, PROCURATION, PROCURATION EXTERNE, DÉCISION D'IRRECEVABILITÉ | 712t al. 1 CC, 712t al. 2 CC, 132 al. 2 CPC (CH)